Nurses' Experiences in Providing Palliative Care to Stroke Patients - Yohanis Jowa Dairu; Maria Syelvrida Tumina; Syahrir Syahrir (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stroke is one of the main diseases that causes long-term disability and increases the need for palliative care. Nurses play a central role in providing palliative nursing care, especially in improving the quality of life of patients experiencing physical, psychological, social, and spiritual disorders. Exploring the experiences of nurses providing palliative care to stroke patients in the Garuda Ward of S.K. Lerik Regional General Hospital in Kupang City. This study used a qualitative method with a phenomenological approach. Data were obtained through in-depth interviews, using purposive sampling technique with 10 nurses as participants. The participant was selected based on inclusion criteria as follow: nurses who have experiences in palliative nursing care for stroke patients. We identified five main themes as follow: (1) Nurses have a good understanding of palliative care, (2) Patience and empathy as the main keys for nurses, (3) Professional responsibility and initiative of nurses, (4) Collaboration and initiatives in providing palliative care, (5 The need for palliative care competency development. Nevertheless, nurses demonstrated strong commitment and high empathy in providing holistic support for stroke patients.